Latitudinal variability of physiological responses to heat stress of the intertidal limpet Cellana toreuma along the Asian coast - YW Dong; GD Han; M Ganmanee; J Wang (My University, 2015)
MEPS Marine Ecology Progress Series Contact the journal Facebook Twitter RSS Mailing List Subscribe to our mailing list via Mailchimp HomeLatest VolumeAbout the JournalEditorsTheme Sections MEPS 529:107-119 (2015) - DOI: https://doi.org/10.3354/meps11303 Latitudinal variability of physiological responses to heat stress of the intertidal limpet Cellana toreuma along the Asian coast Yun-wei Dong1,*, Guo-dong Han1, Monthon Ganmanee2, Jie Wang1 1State Key Laboratory of Marine Environmental Science, College of Ocean and Earth Sciences, Xiamen University, Xiamen, PR China 2Faculty of Agricultural Technology, King Mongkut's Institute of Technology Ladkrabang, Bangkok 10520, Thailand *Corresponding author: dongyw@xmu.edu.cn ABSTRACT: Potential future distribution shifts of intertidal invertebrates along the Asian coast in the face of global change remain unclear. Integrative study that comprise environmental temperature monitoring and comparative physiological study of thermal adaptation among different geographical populations of species are important to identify population-related differences in thermal ecology that could affect the persistence of species in their present distribution ranges. In the present study, in situ operative temperatures were recorded continuously for 5 mo from August 2011 to January 2012, and measurements of lethal temperature, cardiac performance and gene expression were carried out in 3 geographical populations of the limpet Cellana toreuma (tropical shore: Sichang Island, Thailand; subtropical shore: Nanding Island, Zhangzhou, China; temperate shore: Dagong Island, Qingdao, China). Compared to limpets on the tropical shore in Sichang Island with high mean temperature (28.28°C) and narrow thermal range (19.13 to 46.56°C), limpets on the subtropical shore in Nanding Island have to cope with a thermal environment characterized by a wider temperature range (6.42 to 44.98°C). The absence of differences in lethal temperature (LT50) of limpets from all the locations indicates that limpets currently suffer from intensive heat stress across their biogeographic range. Although the populations lacked differences in upper thermal limit, variations were noted among populations in transcriptional responses in genes linked to energy metabolism. Limpets on the subtropical shore in Nanding Island live closer to their upper thermal limits and thus will be very sensitive to future temperature increases. KEY WORDS: Biogeography · Limpet · Body temperature · Physiological response · Rocky intertidal zone Full text in pdf format Supplementary material PreviousNextCite this article as: Dong YW, Han GD, Ganmanee M, Wang J (2015) Latitudinal variability of physiological responses to heat stress of the intertidal limpet Cellana toreuma along the Asian coast. Mar Ecol Prog Ser 529:107-119. https://doi.org/10.3354/meps11303 Export citation RSS - Facebook - Tweet - linkedIn Cited by Published in MEPS Vol. 529. Online publication date: June 08, 2015 Print ISSN: 0171-8630; Online ISSN: 1616-1599 Copyright © 2015 Inter-Research.
Keywords: Limpet; Rocky shore; Intertidal ecology; Physiological and biochemical adaptations